Diabetes Screening Reminder for Women With Prior Gestational Diabetes: A Randomized Controlled Trial. Issue 1 (July 2015) - Zera, Chloe A.; Bates, David W.; Stuebe, Alison M.; Ecker, Jeffrey L.; Seely, Ellen W.
Abstract : OBJECTIVE: To evaluate whether an electronic health record (EHR) reminder improves rates of screening for type 2 diabetes in women with prior gestational diabetes. METHODS: We randomly allocated primary care providers (by clinic site) to a reminder for type 2 diabetes screening within the EHR or to usual care. Women with previous gestational diabetes mellitus were identified through an automated search of laboratory results and the problem list. We compared rates of screening during the study period (2010–2012) in women at intervention sites with those at control sites. With a sample size of 850 participants, we had 80% power to detect a 15% difference in screening rates. RESULTS: We included 847 individuals seen at a participating clinic during the study period, of whom 471 were at a reminder clinic and 376 were at a control clinic. A similar proportion of women were screened for type 2 diabetes in both groups (n=265, 56.3% of the reminder group compared with n=206, 54.8% of the control group, P =.67; adjusted odds ratio [OR] 1.04, 95% confidence interval [CI] 0.79–1.38). Patient characteristics associated with risk for diabetes including body mass index (adjusted OR per kg/m 2 1.05, 95% CI 1.01–1.08) and race (adjusted OR for nonwhite race 2.14, 95% CI 1.57–2.92) were significantly associated with screening. CONCLUSION: A simple EHR reminder did not increase the rate of diabetes screening in women with prior gestational diabetes mellitus. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, www.clinicaltrials.gov, NCT01288144. LEVEL OF EVIDENCE: I Abstract : An electronic health record–based reminder does not improve the rate of diabetes screening in women with prior gestational diabetes.